Beta-Blockers in Pediatric Hypertrophic Cardiomyopathies - Ostman-Smith, Ingegerd (Reviews on Recent Clinical Trials, 2014)
Congestive cardiac failure accounts for 36% of childhood deaths in hypertrophic cardiomyopathy, and in infants with heart failure symptoms before two years of age, the mortality is extremely high unless treatment with betareceptor antagonists is instituted. The mechanism of heart failure is not systolic dysfunction, but rather extreme diastolic dysfunction leading to high filling pressures. Risk factors for development of heart failure are a generalized pattern of hypertrophy with a left ventricular posterior wallto- cavity ratio >0.30, the presence of left ventricular outflow tract obstruction at rest, and the co-existence of syndromes in the Noonan/Leopard/Costello spectrum. The 5-year survival of high-risk patients is improved from 54% to 93% by highdose beta-blocker therapy (>4.5 mg/kg/day propranolol). The mechanism of the beneficial effect of beta-blockers is to improve diastolic function by lengthening of diastole, reducing outflow-obstruction, and inducing a beneficial remodelling resulting in a larger left ventricular cavity, and improved stroke volume. Hypertrophic cardiomyopathy is associated with increased activity of cardiac sympathetic nerves, and infants in heart failure with hypertrophic cardiomyopathy show signs of extreme sympathetic over-activity, and require exceptionally high doses of beta-blockers to achieve effective betablockade as judged by 24 h Holter recordings, often 8-24 mg/kg/day of propranolol or equivalent. Conclusion: Beta-blocker therapy is without doubt the treatment of choice for patients with heart failure caused by hypertrophic cardiomyopathy, but the dose needs to carefully titrated on an individual basis for maximum benefit, and the dose required is surprisingly large in infants with heart failure due to hypertrophic cardiomyopathy.
Keywords: propranolol